Análise do papel da Farmácia Universitária da Universidade Federal Fluminense na dispensação de medicamentos cardiovasculares - Correia, João Márcio da Silva (2012)
In recent years there has been an expansion of chronic degenerative diseases, and among them, stand out as cardiovascular disease. In Brazil, this disease is the leading cause of death in all regions of the country, in both sexes. In this context, deserves attention high blood pressure (hypertension), and that there is a reduction in morbidity and mortality associated with cardiovascular risks of people with hypertension, it is essential to adherence toantihypertensive treatment, ie, non-pharmacological and drugs. Consistent with other health problems in Brazil, there are millions of people without access to medicines. Knowing that the use of drugs has become indispensable to contribution to improving the quality and life expectancy of the population. This study aimed to analyze the role played by FAU in access to cardiovascular drugs by the population of Niterói and its surroundings, discussing the potential complementary nature of the University Pharmacy to public health policies regarding access to medicines for the treatment of cardiovascular diseases. This research will consist of a study of use of cardiovascular medications provided by University Pharmacy of Universidade Federal Fluminense in the period 2008 to 2011. This being a study of observational and retrospective design. The data were collected from the database of the University Pharmacy. We considered the same drugs that University Pharmacy markets and that are freely available at Popular Pharmacy Program. The record of sale of goods was taken as a measure of consumer products. It may be noted that in 2011 there was a significant decrease in sales of cardiovascular drugs, and therefore the numbers of DDD/1000 people assisted. Atenolol 25mg, for example, declined by approximately 80% in the number of drugs commercialized between 2008 and 2011.To identify variables that may influence this consumption, a questionnaire was prepared for use with patients who came to FAU to use any of the drugs listed in the cast of the Popular Pharmacy and linked to the cardiovascular system to understand the reasons why these patients prefer still buy in the drug at FAU than available free of charge by the government. The result has been that most of the 150 people interviewed is composed by a majority of females with a mean age of 65 years, with incomplete primary education, and residents of Niterói with income up to a minimum wage. The main reasons given to continue buying their drugs from the FAU involved the low price of medicines (30,93%), good service (18,87%) and good quality products (16,08%). Thus, one can consider that the FAU has played a complementary role to government policies on access to cardiovascular drugs